POTENTIAL TOURISM DEVELOPMENT OF SANDS TIKU REGENCY OF WEST SUMATERA PROVINCE - Ilbi Candra Yani; Dessy Yoswaty; Afrizal Tanjung (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
Abstract This research aims to: to know the potential of Pasia Tiku beach to be developed as marine ecotourism area, and to make tourism development strategy of Pasia Tiku beach as maritime tourism. Pasia Tiku beach as one of the beaches located in Agam Regency West Sumatera Province is assumed to have marine tourism potential which is very nice. The existing tourist attraction has not been developed optimally and has not been managed properly by the manager to make Pasia Tiku Beach as a maritime tourist attraction by tourists. Method used in this research is survey method that is by way of direct observation to the field and measure the data which is needed qualitatively and quantitatively.Based on the calculation of total score and weight of IFE and EFE obtained respectively of 2.75 and 2.96. Total IFE <EFE above 2.5 then the external factor condition is stronger than its internal factor. It can be concluded that in developing marine tourism area at Pasia Tiku beach to pay attention is the strong external factor to get chance at the time of development. The ecotourism development strategy at Pasia Tiku beach is to create environmental action action program, make zoning tour plan, create tourist attraction that has cultural value while maintaining the authenticity of tourist area. It then improves coordination with various parties to provide training and improve the development of facilities and infrastructure, enhance the creativity of local communities in tourism businesses that do not provide environmental change, take advantage of the authenticity and naturalness of the beach and enhance tourist attractions to attract local and foreign tourists to come to Pasia beach Tiku. Keywords: Tourism Potential, Tourism Development, Marine Tourism.